Bipolar fluorophores based on intramolecular charge-transfer moieties of sulfone for nondoped deep blue solution-processed organic light-emitting diodes. (May 2020) - Cao, Liang; Zhang, Lei; Wei, Qiang; Zhang, Jiasen; Chen, Dongjun; Wang, Sheng; Su, Shi-jian; Wang, Tao; Ge, Ziyi
Abstract: Dipolar emitters exhibited excellent performance in organic light-emitting diode (OLED). However, these molecules had intramolecular charge-transfer (ICT) properties, which posed challenge to obtain deep blue emission. In this study, three fluorophores were designed by introducing carbazole and diphenylamine as electron donors and sulfone as electron acceptor due to their mild charge-accepting properties and twisted angles. These materials appeared almost in vertical angles of the dihedral configuration, and exhibited high thermal and electrochemical stability, suitable for solution-processed OLED. The solution-processed non-doped devices based on these three emitters were realized, where two emissions within the standard deep blue emission range were achieved with the Commission International e de l'Eclairage (CIE) coordinates of (0.16, 0.12) and (0.16, 0.15). Highlights: Two deep-blue electroluminescence were designed and synthesized which with the CIEx, y of (0.16, 0.12) and (0.16, 0.15). These materials appeared almost vertical angles of the dihedral configuration. These materials exhibited high thermal and electrochemical stability. The OLED devices of this article were fabricated through solution-process with nondoped.